Tren Perkembangan Komoditi Unggulan Perkebunan Rakyat di Sumatera Barat - Idrus, Rusda Khairati (Jurnal Ekonomi, 2012)
This research is held with objectives: 1) to see the trend planted area and production of rubber, coconut, coffee, cacao, cassievera and gambir as superior and specific plantation small holder plantation in West Sumatra; 2) to forecast the planted area and production of these commodity in the next five years. The objectives are reached through regression method using time series secondary data of planted area and production from year 2002 to 2011, depends on available. The result show that the trends of planted area for rubber, cacao, gambir are increasing every year with amount: 3.295,303 ha for rubber; 163,382 ha for coconut; 16.396,743 ha for cacao and 459,503 ha for gambir. Based on their trends, in the year 2016 planted area for rubeer is estimated will be 180.398 ha, coconut 92.331 ha, cacao 195.392 ha, and gambir will be 23.956 ha.